Military and Political Studies - A. I. Podberyozkin (MGIMO University Press, 2014)
Military-political issues is an important area of research work at MGIMO. The difference in this direction from the classical international specialization is that it is at the intersection of several disciplines: military science, military-technical and military-industrial as well as International Relations. A specialist in military and political issues should not only be an expert in the field of international relations and diplomacy, but also have a deep knowledge of military-technical issues to understand the basic trends in the development of scientific and technological progress and its impact on the balance of forces in the world. Global changes in the balance of power and the nature of the conflict, the emergence of new types of weapons are changing the basic methods and approaches to the art of war, which requires a science-based perspective on problem solving and multi-disciplinary approach in achieving the goals. Military and political studies allow us to understand how the development of military technology and military organization of the state affected by the political situation in the world, the national security of the country and its place in the system of international relations. Military-political research has been developing at MGIMO for a few decades. It laid down the basis for a scientific school of political-military studies. Its founding fathers were such prominent scholars of international affairs, as I.G. Usachyov, A.D. Nikonov, A.G. Arbatov, V.G. Baranovsky, V.M. Kulagin, A.N. Nikitin and other well-known experts. Their work covers a wide range of military and political issues, including the topics of arms control and disarmament, international, and especially European security, military policy, NATO, the Western military-political doctrines and their practical application. Now the lead in the development of this research at MGIMO has taken Center for Military-Political Studies, which became a concentration of relevant information, knowledge and expertise. The center was established in 2012 with the financial support of Air Defense Concern "Almaz-Antey". The Center is headed by Vice-Rector of MGIMO professor A.I.Podberezkin.